Kebijakan Perusahaan Tentang Upah Ketenagakerjaan di Indonesia Perspektif Maqashid Al-Syariah - Ghufron, Moh. Idil (Fakultas Sosial dan Humaniora, 2020)
This paper aims to see the government's policy in setting regional minimum wage rules which will become the company's guidance in determining employee salary Maqashid Al-Shariah perspective. The minimum wage policy is implemented by the government to minimize violations of labor standards in Indonesia. Determination of arbitrary salaries by the company so as to fail to realize a society that is separated from the poverty line. The minimum wage policy should refer to the Constitution which is clearly described in the 1945 Constitution Article 27 paragraph 2 said that everyone deserves decent employment and livelihood. The Company has the right to hire employees in accordance with company rules by referring to the minimum salary amount in accordance with government regulations, in which case the company has the freedom to determine the salary of employees. In Islam, freedom is not necessarily free of all, freedom in Islam is still bound and must refer to the realization of the value of Maqashid Al-Shariah. So the government policy in determining the policy of minimum wages of employees must be based on the benefit that will create a mutual prosperity